P295 Hocus Pocus: The Role Of Hand-Held Ultrasonography In Predicting Disease Extension And Endoscopic Activity In Ulcerative Colitis. (30th January 2023) - Rispo, A; Calabrese, G; Testa, A; Patturelli, M; Imperatore, N; Nardone, O M; Guarino, A D; Cantisani, N M; Toro, B; Castiglione, F
Abstract: Background: Ulcerative colitis (UC) diagnosis and monitoring still require ileo-colonoscopy (IC) as the reference standard. Bowel sonography (BS) has recently emerged as a non-invasive assessment tool, and Milan Ultrasound Criteria (MUC) score has been validated to estimate and predict UC disease activity. Recently, hand-held BS (HHBS) has been used effectively in several clinical settings (e.g. cardiology, orthopedy, gynaecology), while data about its use in UC are still limited. We aimed to evaluate the diagnostic accuracy of HHBS compared to conventional bowel sonography (BS) in predicting UC extension and activity compared to endoscopy. Methods: From November 2021 to September 2022, we prospectively enrolled consecutive UC patients afferent to our third-level IBD Unit for IC evaluation. Patients underwent IC, HHBS, and BS, and the operators were blinded by the other procedure results. Endoscopy was considered the reference standard for UC extension. Cohen's k test was applied after MUC dichotomization to test the concordance between BS-MUC and HHBS-MUC following Allocca et al. (MUC >6.2: yes/no). Results: At the end of the study, 86 patients with UC were examined. No significant difference was recorded between BS and HHBS in terms of UC at the per-segment extension (p: N.S.) (table 1), and both procedures were comparable regarding colonic wall thickness (CWT) and colonic wall pattern (CWP) assessment (figure 1 and 2). Regarding the prediction of endoscopic activity, BS and HHBS displayed excellent agreement when applying the MUC score system (k = 0.86, p<0.01) (figure 3). Conclusion: Hand-held bowel sonography and BS are comparable in defining UC extension and MUC evaluation in the UC setting. HHBS could be reliable for detecting disease activity and estimating its extension, providing close monitoring of the treat-to-target paradigm. It also represents a non-invasive, easily practicable investigation during a physical examination, allowing immediate medical decisions with significant time and cost advantages.